Pemberian Tepung Daun Salam (Syzygium polyanthum (Wight) Walp.) dalam Ransum Sebagai Bahan Antibakteri Escherichia coli terhadap Organ Dalam Ayam Broiler - W Hermana; D I Puspitasari; K G Wiryawan; S Suharti (Media Peternakan, 2008)
The objective of the present experiment was to evaluate the utilization of bay leaf (Syzygium polyanthum (Wight) Walp.) in the diets as antibacterial agent and its effect on the weight viscera organ of broilers. The experiment was arranged in a completely randomized design with six treatments and three replications. One hundred and eighty birds of five week-old broiler were used in the present experiment, and thirty six birds were decapitated to measure the weight of viscera. On day four, experimental animals were divided into six group of treatments and were provided standard diet. The treatments were as follows, Escherichia coli (E.coli)-uninfected broiler without bay leaf (R0/positive control goup), E. coli-infected broiler without bay leaf (R1/negative control group), R1 + 1% bay leaf (R2), R1 + 2% bay leaf (R3), R1 + 3% bay leaf (R4), and R1 + 0.02% tetracycline (R5). The results showed that weight percentage of liver, spleen, heart, pancrease, bile and intestine were not affected by the addition of 1, 2 and 3% bay leaf (R2,R3 and R4) as compared to those of R0, R1 and R5. However, gizzard percentage of broiler given 3% bay leaf (R4) increased (P < 0.01) to the value same as that of R0 (2.31 vs 2.71%). The highly significant (P < 0.01) increased in weight percentage of kidney was also found due to the treatments, and the increase was significant (P < 0.05) when R5 compared to R2 and R4. The addition of 2% (R3) and 3% (R4) bay leaf and 0.02% tetracycline (R5), as compared to R0, R1 and R2, could depress the number of E. coli in the excreta. In conclusion, the addition of bay leaf up to 3% was able to minimize the number of E. coli in excreta without negatively affecting weight of viscera of broiler chickens. Key words: Syzygium polyanthum (Wight) Walp., tetracycline, Escherichia coli, viscera